2010
DOI: 10.1177/1947603510392022
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown Epithelial Membrane Protein 1 Suppresses Human Degenerative Intervertebral Disc–Derived Nucleus Pulposus Cell Proliferation

Abstract: Objective:Our previous work showed that epithelial membrane protein 1 (EMP1) is highly expressed in nucleus pulposus of the human degenerative intervertebral disc. The present study was designed to investigate the role of EMP1 in nucleus pulposus cells in intervertebral disc degeneration (IDD).Design:Human nucleus pulposus cells derived from degenerative intervertebral discs were cultured. EMP1 expression was knocked down by lentivirus-mediated specific interfering RNA. Cell morphology was observed, and cell p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…In these cancers high endogenous EMP1 expression correlates with poor patients’ outcome. In line with these findings, silencing EMP1 in chondrocytes inhibits cell proliferation [41].…”
Section: Discussionmentioning
confidence: 71%
“…In these cancers high endogenous EMP1 expression correlates with poor patients’ outcome. In line with these findings, silencing EMP1 in chondrocytes inhibits cell proliferation [41].…”
Section: Discussionmentioning
confidence: 71%
“…NPCs are one of the most important components of IDD. NPCs proliferation inhibition and apoptosis directly induce IDD [19][20][21]; thus, the molecular mechanism of NPCs proliferation and apoptosis should be closely related to IDD pathogenesis. In this study, 52 differentially expressed miRNAs were identi ed with |fold change| >2 and P < 0.05.…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial membrane protein 1 ( EMP-1 ) gene belongs to the peripheral myelin protein ( PMP )-22 family, also named as CL-40 , tumor-associated membrane protein ( TMP ), and B4B [ 8 , 9 ]. It has been reported that EMP-1 plays an important role in various cellular processes.…”
Section: Introductionmentioning
confidence: 99%